2017
DOI: 10.18203/2394-6040.ijcmph20170258
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity among mine workers: a cross sectional study in Chitradurga, Karnataka, India

Abstract: Work-related morbidity and mortality not only results in suffering and hardship for the worker and his or her ABSTRACT Background: Workers represent half the world's population and are the major contributors to economic and social development. Their health is determined not only by workplace hazards but also by social and individual actors and access to health services. Work-related morbidity and mortality result in suffering and hardship for worker as well as to his or her family. Thus occupational health of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 7 publications
1
11
2
Order By: Relevance
“…According to work experience 51.07% (41.85% underground workers + 9.22% surface workers) workers are having experience of working for 20-30 yrs and 38.30% (30.50% underground workers + 7.80%) workers are having experience of working for more than 30 yrs which shows that these workers are more exposed to coal dust for a long period and are more prone for chronic diseases when compared to Rajashekar et al 9 A study was done in 493 mine workers where there are no workers who had work experience for more than 20yrs and there are only 4.40% of workers having work experience for 11-20 yrs who are very less compared to our study also in Considine et al study there are only 37.7% of workers having work experience for more than 10 yrs. 7 In the current study, 26.23% (19.85% underground workers and 6.38% surface workers) of workers had a habit of smoking, 68.08% (56.73% underground workers and 11.35% of surface workers) had a habit of regular consumption of alcohol and 6.37% (4.25% underground workers and 2.12% surface workers) of workers had an habit of intake of smokeless tobacco which are the major risk factors causing chronic diseases.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…According to work experience 51.07% (41.85% underground workers + 9.22% surface workers) workers are having experience of working for 20-30 yrs and 38.30% (30.50% underground workers + 7.80%) workers are having experience of working for more than 30 yrs which shows that these workers are more exposed to coal dust for a long period and are more prone for chronic diseases when compared to Rajashekar et al 9 A study was done in 493 mine workers where there are no workers who had work experience for more than 20yrs and there are only 4.40% of workers having work experience for 11-20 yrs who are very less compared to our study also in Considine et al study there are only 37.7% of workers having work experience for more than 10 yrs. 7 In the current study, 26.23% (19.85% underground workers and 6.38% surface workers) of workers had a habit of smoking, 68.08% (56.73% underground workers and 11.35% of surface workers) had a habit of regular consumption of alcohol and 6.37% (4.25% underground workers and 2.12% surface workers) of workers had an habit of intake of smokeless tobacco which are the major risk factors causing chronic diseases.…”
Section: Discussionmentioning
confidence: 83%
“…Hypertension, diabetes and chronic respiratory symptoms are more prevalent in coal miners than normal population. 9,13 There is limited literature regarding morbidity pattern in coal mines. This study was conducted with the objective to know the working pattern of coal mine workers and to know their habits and morbidity pattern.…”
mentioning
confidence: 99%
“…(2018) has also reported similar level of work experience among mine workers. 3 Contrary to this Rajashekar S et al (2017) has reported that majority of the mine workers in Karnataka had total work experience of five years. 13 The mean years of working in the present study was 16.71 ± 9.72 years which is lower than the mean years of work reported by Ahmad A (2015) 14 and Shamim M et al (2017).…”
Section: Demographic and Occupational Profiling Of Mine Workersmentioning
confidence: 83%
“…3 Contrary to this Rajashekar S et al (2017) has reported that majority of the mine workers in Karnataka had total work experience of five years. 13 The mean years of working in the present study was 16.71 ± 9.72 years which is lower than the mean years of work reported by Ahmad A (2015) 14 and Shamim M et al (2017). 11 Mine workers were involved in various activities in the mines from drilling, blasting, cutting of stones to carrying the stones, loading the stones in the vehicles, cleaning of the waste material.…”
Section: Demographic and Occupational Profiling Of Mine Workersmentioning
confidence: 83%
See 1 more Smart Citation